Artemisinin Attenuates Transplant Rejection by Inhibiting Multiple Lymphocytes and Prolongs Cardiac Allograft Survival - Yang, Zhe; Han, Fei; Liao, Tao; Zheng, Haofeng; Luo, Zihuan; Ma, Maolin; He, Jiannan; Li, Lei; Ye, Yongrong; Zhang, Rui; Huang, Zhengyu; Zhang, Yannan; et al. (Frontiers in Immunology, 2021)
Immunological rejection is an important factor resulting in allograft dysfunction, and more effective therapeutic strategies need to be explored to improve allograft outcomes. Many studies have indicated that artemisinin exerts immunosuppressive effects, apart from being an anti-malarial agent. In this study, we investigated the therapeutic effect of artemisinin for rejection in a rat cardiac transplantation model. We found that it markedly attenuated allograft rejection and injury histologically and significantly prolonged allograft survival. Upon further exploring the mechanism, we demonstrated that artemisinin not only attenuated T cell-mediated rejection (TCMR) by reducing effector T cell infiltration and inflammatory cytokine secretion and increasing regulatory T cell infiltration and immunoregulatory cytokine levels, but also attenuated antibody-mediated rejection (ABMR) by inhibiting B cell activation and antibody production. Furthermore, artemisinin also reduced macrophage infiltration in allografts, which was determined to be important for TCMR and ABMR. Moreover, we demonstrated that artemisinin significantly inhibited the function of pure T cells, B cells, and macrophages in vitro. Taken together, the findings of this study indicate that artemisinin significantly attenuates TCMR and ABMR by targeting multiple effectors. Therefore, this agent might have potential for use in clinical settings to protect against transplant rejection.